Comparison of γ‐aminobutyric acid accumulation capability in different mung bean (Vigna radiata L.) varieties under heat and relative humidity treatment, and its correlation with endogenous amino acids and polyamines. (1st September 2020) - Ma, Yuling; Tong, Litao; Li, Juan; Ashraf, Jawad; Wang, Shanshan; Zhao, Bo; Liu, Liya; Blecker, Christophe; Zhou, Sumei
Summary: In this study, the accumulation of GABA and its inherent factors across different varieties of mung bean ( Vigna radiata L.) in response to heat and relative humidity (HRH) were investigated. Results showed the average GABA content in mung bean varieties was increased 7.52 times following HRH treatment, and the black mung bean variety (A8) exhibited the highest GABA accumulation capability (1.76–84.57 mg per 100 g DW). From the perspective of GABA shunt metabolites, the free glutamic acid content of mung beans significantly decreased ( P  < 0.05) after HRH treatment and presented a significant correlation ( P  < 0.05) with GABA content. In polyamine degradation pathway, although the average levels of spermine and spermidine of mung bean varieties significantly decreased ( P  < 0.05) after HRH treatment, no significant correlation with GABA content was identified. Hence, the GABA accumulation was predominantly attributed to GABA shunt. Besides, free amino acids including glutamic acid, serine, ornithine, arginine and glycine in mung beans showed a significant positive correlation ( P  < 0.05) with GABA content and increment following HRH treatment, which suggested that mung beans enriched in these free amino acids might accumulate higher amounts of GABA after HRH treatment and be useful for industrial applications. Abstract : Graphical abstract for enriching GABA in mung bean